Analyzing the Gender Strategy in Math: Good, Routine, or Naive Problem Solver? - Dwiyani, Suci; Nanna, A.Wilda Indra; Kusnadi, Dedi (Universitas PGRI Madiun, 2021)
Each student's problem solving has different characteristics and can be seen in terms of gender differences. Gender in mathematics achievement is still a hot topic to be researched. Therefore, this study aims to describe the problem solving of primary school students on Geometry using the Polya strategy model in terms of gender. This study uses a qualitative approach design. Participants in this study consisted of 4 high and moderate achievement primary school students of the male and female gender. Data collection providing by problem-solving test, and then we conducted interviews with participants as part of the data triangulation process. Based on the study results, we found that: (1) there are differences in problem-solving strategies carried out by male and female students. For high achievement, male participants are superior, while for moderate achievement, female participants are superior; (2) A male student with high achievement is a good problem solver. A female student with moderate achievement is routine problem-solver, and naive problem-solvers are a female student with high achievement and a male student with moderate achievement. (3) Good problem solver were confident and able to find other ways when encounters obstacles. Routine problem solver do not do the looking back process, so there are mistakes at some of the problem-solving stages, and naive problem solvers only manipulate the numbers on the problem into some calculation operations.